If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5 + -15 = 7y + 9 Combine like terms: -5 + -15 = -20 -20 = 7y + 9 Reorder the terms: -20 = 9 + 7y Solving -20 = 9 + 7y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-7y' to each side of the equation. -20 + -7y = 9 + 7y + -7y Combine like terms: 7y + -7y = 0 -20 + -7y = 9 + 0 -20 + -7y = 9 Add '20' to each side of the equation. -20 + 20 + -7y = 9 + 20 Combine like terms: -20 + 20 = 0 0 + -7y = 9 + 20 -7y = 9 + 20 Combine like terms: 9 + 20 = 29 -7y = 29 Divide each side by '-7'. y = -4.142857143 Simplifying y = -4.142857143
| 2(1.6x)-1.33=-x+4.13 | | 4z+17=3z+4 | | 5-2x-4x=9 | | 27(2/3n) | | 500/3000 | | 7/3xb^4 | | y=-15-(-2)-(11-6) | | 2x^2y+4xy-58y=0 | | y=-20+30-40-(-50) | | (10-y)+y=3.09 | | y=x^3+2x^2-8x-5 | | (9+z)(5z+3)=0 | | 5x^3+40x^2+60x=0 | | Z=23 | | 2x-8+2=x-3+5 | | f(x)=x^3+2x^2-8x-5 | | 4x(2x-1)^1/2 | | n^2-19n+10=0 | | 7(3-z)6=-z | | 1/3x+2=1/6x+4/3 | | 3y=2x+b | | 3(x+7)-2x=3+2x | | Y=x^4-3x^2 | | 28=4b-3s | | -3+5x+30=37 | | 28=4b+3s | | -8(3+r)=32 | | 3/3-4 | | -3(2h+1)=4h-3 | | .15-c=1.105 | | -3(-5)(-7)(-1)= | | -8(3+r)=42 |